Correction: Rapid determination of the tumour stroma ratio in squamous cell carcinomas with desorption electrospray ionization mass spectrometry (DESI-MS): a proof-of-concept demonstration. Issue 18 (1st September 2017) - Woolman, Michael; Tata, Alessandra; Dara, Delaram; Meens, Jalna; D'Arcangelo, Elisa; Perez, Consuelo J.; Prova, Shamina Saiyara; Bluemke, Emma; Ginsberg, Howard J.; Ifa, Demian; McGuigan, Alison; Ailles, Laurie; et al.
Abstract : Correction for 'Rapid determination of the tumour stroma ratio in squamous cell carcinomas with desorption electrospray ionization mass spectrometry (DESI-MS): a proof-of-concept demonstration' by Michael Woolman et al., Analyst, 2017, 142, 3250–3260.